THE RELATIONSHIP OF INDIVIDUAL CHARACTERISTIC WITH THE INCIDENCE OF PULMONARY TUBERCULOSIS IN ADULTS IN THE COASTAL AREA OF WEST SUMATERA IN 2022 - Annisa Novita Sary; Oktariyani Dasril; Eliza Trisnadewi; Edison Edison; Gusliani Eka Putri (Jurnal Kesehatan Medika Saintika, 2022)
ABSTRACTTuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and TB is the highest infectious killer in the world. In 2019, 1.4 million people died from TB. The results of the preliminary study of residents living in coastal areas obtained that the health of the home environment was still some who did not meet the requirements of a healthy home. Based on the report of the West Sumatra Provincial Health Office in 2018, TB cases were found with a Crude Death Rate (CDR) of 42.8%. The highest prevalence of TB cases in West Sumatra was found in Padang City with a total of 6,464 cases in 2018. Followed by Pesisir Selatan Regency with 3,176 cases. The purpose of this study was to determine the relationship between individual characteristics and the incidence of pulmonary tuberculosis in adults in the coastal areas of West Sumatra Province. The research method is analytic observational with a case control study design. The sample in this study amounted to 200 consisting of 100 cases and 100 controls. The dependent variable is the incidence of pulmonary TB and the independent variable is individual characteristics consisting of age, gender, type of work, and level of education. Primary data were collected using a questionnaire and analyzed by univariate and bivariate with chi-square test, with 95% confidence level, p<0.05. The results of statistical tests with chi-square showed that there was a relationship between type of work (p-value=0.028) and education level (p-value=0.031) with the incidence of pulmonary TB. Meanwhile, age and gender did not have a relationship with the incidence of pulmonary TB with p>0.05. It can be concluded that occupation and level of education pose a significant risk to the incidence of Pulmonary TB in Adults in the Coastal Region of West Sumatra in 2022. One way that can be done is the need for an active role from health workers in the form of counseling about pulmonary TB disease to the community in order to improve endurance, apply and increase vigilance by taking into account the factors that cause pulmonary TB.